Near-perihelion activity of comet 67P/Churyumov-Gerasimenko. A first attempt of non-static analysis - Skorov, Yuri; Keller, H Uwe; Mottola, Stefano; Hartogh, Paul (Monthly Notices of the Royal Astronomical Society, 2020)
The observed rate of water production of comet 67P/Churyumov–Gerasimenko near its perihelion can be approximated by a very steep power function of the heliocentric distance. Widely used thermophysical models based on a static dust layer on top of the icy/refractory matrix are poorly consistent with these observations. We analyse published model results and demonstrate that thermophysical models with a uniform and static ice free layer do not reproduce the observed steep water production rates of 67P near perihelion. Based on transient thermal modeling we conclude that the accelerated gas activity can be explained assuming that the active area fraction near the south pole is increased. The deeper penetration of the heat wave during polar day (no sunset) can activate sublimation through thicker inert dust layers. This can also lead to removal of thicker dust layers and consequently to an expansion of the active area.